Penerapan Metode Pembelajaran Audio Lingual Method (ALM) dalam Mengembangkan Kemampuan Berbahasa Inggris Warga Belajar di Lembaga Kursus Bahasa Inggris PEC Kedaung Kaliangke Kota Jakarta Barat - Rachmanda, Rifda; Sholih, Sholih; Rosmilawati, Ila (ALSYS, 2025)
English language learning particularly in the core communicative skills of speaking and listening continues to face various challenges in many non-formal education institutions. This study aims to (1) describe the implementation of the Audio Lingual Method (ALM) in developing the English language proficiency of learners at the PEC English course in Kedaung Kaliangke, West Jakarta, and (2) evaluate the learners’ English proficiency following the application of this method. A qualitative descriptive approach was employed, with data collected through observation, interviews, and documentation. Informants included one branch manager who also served as a tutor, one receptionist who also served as a tutor, two instructors, and twelve learners. The findings indicate that the application of ALM was moderately successful, as it followed key phases such as repetition, drills, memorization, and imitation practices that promote habit formation in language use. Indicators of English proficiency included listening skills (covering recall, comprehension, application, and analysis) and speaking skills, particularly in responsive and imitative forms. The study concludes that ALM is effective in enhancing practical and applicable language skills. The implication is that this method is recommended for consistent use in non-formal educational settings to improve the quality of communicative and practice-oriented language learning outcomes.